Access and Expansion of Educational Opportunity in India With Reference to Higher Education - Abhai Maurya (Atlantis Press, 2014)
Access, or rather non-access to higher education in India has been prevailing in many forms. The Gross Enrollment Ratio (GER) to HE in India has not even reached 15% of the population by 2010. The University Grants Commission of India, which is responsible for the growth or non-growth of Higher education in India, has worked out the measures such as opening 30 more central universities and numerous state, private and deemed universities and colleges, particularly in rural and hazardous backward areas, with a view to increasing the GER in Indian HE. However, there are inherent 'left-outs' from Indian HE which the powers have failed to address. These 'left-outs'are caused by the factors like rural-urban disparities, gender disparities, inter-religious disparities, inter-class disparities, inter-caste disparities, inter-state and regional disparities, age disparities and the disparities facing differently-abled persons, disparities caused by skills or non-skills in English language. In our paper we analyze the lengthy, marshaling facts and figures and the causes generating these disparities. At the end we may also discuss how one particular university had sought to overcome the above-mentioned disparities and handicaps.